Sejarah dan Perkembangan Pertanggungjawaban Korporasi - Hesti Widya Ningrum (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2018)
Corporate criminal responsibility has a difference in its development between countries with the common law system and those with civil law system. This is also, no exception in Indonesia. Indonesia as a Dutch Colony, which adheres to the civil law system which carries the adagium "deliquere non potest university," where corporations cannot be convicted. By using a normative approach, this article discusses about corporation as subject of criminal law which regulated outside the Criminal Code (KUHP). In Pratice, there have been several cases that punish corporations who commit criminal acts such as corruption. The finding of this article is court in Indonesia, especially corruption court are more likely to use the doctrine of vicarious liability as in common law countries. Contrary, with the conception in the Draft Criminal Code (RKUHP) that is more likely to use identification doctrine on corporate responsibility.